Painting the landscape with fire longleaf pines and fire ecology - Latham, Den (University of South Carolina Press, 2013)
"Fire can be a destructive, deadly element of nature, capable of obliterating forests, destroying homes, and taking lives. Den Latham's Painting the Landscape with Fire describes this phenomenon but also tells a different story, one that reveals the role of fire ecology in healthy, dynamic forests. Fire is a beneficial element which allows the longleaf forests of America's Southeast to survive. In recent decades, foresters and landowners have become intensely aware of the need to "put enough fire on the ground" to preserve longleaf habitat for red-cockaded woodpeckers, quail, wild turkeys, and a host of other plants and animals. Painting the Landscape with Fire is a hands-on-primer for those who want to understand the role of fire in longleaf forests. Latham joins wildlife biologists, foresters, wildfire fighters, and others as they band and translocate endangered birds, survey snake populations, improve wildlife habitat, and conduct prescribed burns on public and private lands. Painting the Landscape with Fire explores the unique southern biosphere of longleaf forests. Throughout, Latham beautifully tells the story of the resilience of these woodlands and of the resourcefulness of those who work to see them thrive. Fire is destructive in the case of accidents, arson, or poor policy, but with the right precautions and safety measures, it is the glowing life force that these forests need"--